2019
DOI: 10.3390/medicina55100670
|View full text |Cite
|
Sign up to set email alerts
|

Diuretic Enhanced Ultrasonography in the Diagnosis of Pyeloureteral Obstruction

Abstract: Background and Objectives: To determine the value of diuretic ultrasonography for the diagnosis of obstructive hydronephrosis. Materials and Methods: Diuretic enhanced ultrasonography was used routinely as a part of examination of patients with hydronephrosis in our Department. There were 72 patients (42 males, 30 females; aged 2 months to 17 years; median age 7.07 years) with a sonoscopic diagnosis of hydronephrosis included from January 2006 until October 2011. The anteroposterior diameter (AD) of renal pelv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…They have highlighted that the use of these spices as complementary medicine in UTIs may be worthy of consideration [27]. Kazlauskas et al determined the value of diuretic ultrasonography in the diagnosis of obstructive hydronephrosis in a cohort of 72 patients (in the study population, hydronephrosis was more commonly unilateral [84.7%, n = 61]); as a result of their study, the authors have concluded that diuretic ultrasonography used as an adjunctive investigation method may aid in the prediction of obstructive hydronephrosis [28].…”
mentioning
confidence: 99%
“…They have highlighted that the use of these spices as complementary medicine in UTIs may be worthy of consideration [27]. Kazlauskas et al determined the value of diuretic ultrasonography in the diagnosis of obstructive hydronephrosis in a cohort of 72 patients (in the study population, hydronephrosis was more commonly unilateral [84.7%, n = 61]); as a result of their study, the authors have concluded that diuretic ultrasonography used as an adjunctive investigation method may aid in the prediction of obstructive hydronephrosis [28].…”
mentioning
confidence: 99%
“…Ageing results in decline of kidney function at an approximate rate of 1 mL/min per year at age 40 years to ahead. Women experience quicker rate of decline when compared to men regarding this ageing parameter [17].…”
Section: Discussionmentioning
confidence: 99%
“…Aging results in the decline of kidney function at an approximate rate of 1 mL/min per year from age 40 years to ahead. Women experience a quicker rate of decline when compared to men regarding this aging parameter [8].…”
Section: Discussionmentioning
confidence: 99%